2022
DOI: 10.3389/fnins.2022.917300
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Alpha Asymmetry in Response to Stressor Moderates the Relation Between Parenting Hassles and Child Externalizing Problems

Abstract: Inequitable urban environments are associated with toxic stress and altered neural social stress processing that threatens the development of self-regulation. Some children in these environments struggle with early onset externalizing problems that are associated with a variety of negative long-term outcomes. While previous research has linked parenting daily hassles to child externalizing problems, the role of frontal alpha asymmetry (FAA) as a potential modifier of this relationship has scarcely been explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 122 publications
(183 reference statements)
0
8
0
Order By: Relevance
“…In addition, we did not expect a significant association between right frontal alpha asymmetry and externalizing problems (H2b). Previous research has found a relation between right frontal alpha asymmetry and internalizing problems in children (e.g., Lopez-Duran et al, 2012;Mulligan et al, 2022). Past literature examining the relations between right frontal alpha asymmetry and externalizing problems has not found a link between these variables (see review by Thibodeau et al, 2006).…”
Section: Current Studymentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, we did not expect a significant association between right frontal alpha asymmetry and externalizing problems (H2b). Previous research has found a relation between right frontal alpha asymmetry and internalizing problems in children (e.g., Lopez-Duran et al, 2012;Mulligan et al, 2022). Past literature examining the relations between right frontal alpha asymmetry and externalizing problems has not found a link between these variables (see review by Thibodeau et al, 2006).…”
Section: Current Studymentioning
confidence: 99%
“…A possible neural mechanism that may act as a mediator in this relation is frontal alpha asymmetry, which has been associated with psychopathology in children and adults (Feng et al., 2012). In addition, maternal internalizing psychopathology and SES have also been associated in studies examining the development of frontal alpha asymmetry in children; however, this research has been mostly limited to concurrent associations and relatively small samples that may not be powered to detect potential associations (e.g., Gatzke‐Kopp et al., 2014; Lopez‐Duran et al., 2012; Mulligan et al., 2022; Peltola et al., 2014). The current preregistered study aimed to address these gaps in the literature by examining the association between prenatal maternal internalizing symptoms, children's frontal alpha asymmetry, and internalizing and externalizing outcomes in a large sample of children.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations